Perinatal Risk Factors in Children Diagnosed with Autism Spectrum Disorder in Dubai: A Case-Control Study - Hussein Adamjee Burhani; Sara Hussain; Jeyaseelan Lakshmanan; Ammar Albanna (Dubai Medical Journal)
Introduction: Autism spectrum disorder (ASD) is a heterogeneous disorder characterized by deficits in social-emotional reciprocity and associated behavioral symptoms. The goal of this study was to examine perinatal risk factors for ASD and their correlates in a tertiary care hospital in Dubai, United Arab Emirates (UAE). Methods: We conducted a case-control study of 87 children diagnosed with ASD using the DSM-5 criteria, who were born between 1999 and 2014, and diagnosed between 2014 and 2016, and 134 age- and gender-matched control subjects. Data were collected from hospital medical records. Associations between ASD and maternal, birth, and neonatal risk factors were examined using logistic regression analysis. Results: Maternal fever was associated with ASD (p = 0.018), with 0% in the control group and 5% in the cases. Multivariate logistic regression analysis revealed a trend for an association between high birthweight (>4,000 g) and ASD (95% CI: 0.76–59.93, p = 0.086). Conclusion: The data affirmed the established gender difference of approximately four males to one female and supported previous findings associating ASD with prematurity. Larger representative studies are further required to explore risk factors for ASD in the UAE.